Vrnitev mladostnikov v šolo po nezgodni možganski poškodbi - Sagadin, Maja (Rehabilitacija (Ljubljana), 2012)
The most endangered age group for traumatic brain injury is youth between 15 and 30 years of age. There are different causes for brain injuries. Adolescent are most often injured in traffic, at sports or in violent attacks. Recovery after brain injury is long-term and uneven. Consequences can last a long time and can prevent integration among peers and in every day activity. After release from rehabilitation institution the recovery is normally not over, but is continued at home and often also in the educational environment. When we assess that adolescent will be able to continue education after rehabilitation, we adjust our rehabilitation goals and course of therapy. Long-term experiences show that longer monitoring and maintenance of contacts among rehabilitation professionals and school workers are crucial for successful continuation of education after traumatic brain injury. In article we present two cases of returning to school after traumatic brain injury.
Keywords: Brain Injuries; education; individually adapted education; izobraževanje; možganske poškodbe; okrevanje; recovery; rehabilitacija; rehabilitation; traumatic brain injury; vocational rehabilitation